1997
DOI: 10.1590/s0100-879x1997000700004
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin in the ascitic fluid of cirrhotic patients: correlation with biochemical risk factors for the development of spontaneous bacterial peritonitis

Abstract: Cirrhotic patients (23 with alcoholic cirrhosis, 5 with posthepatitic cirrhosis and 2 with cryptogenic cirrhosis) with ascites and portal hypertension were studied and divided into two groups corresponding to high or low risk to develop spontaneous bacterial peritonitis (SBP) related to the concentration of total protein in the ascitic fluid (A-TP): group I (high risk): A-TP≤1.5 g/dl and group II (low risk): A-TP>1.5 g/dl. Fibronectin (FN), C3 and C4 concentrations were measured by radial immunodiffusion while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Because of its relatively simple composition [2], ascites has generally been considered to have little influence on the hemodynamic, and host defense abnormalities occurring in cirrhotic patients. This concept, however, has recently been challenged by several investigations describing significant amounts of proinflammatory cytokines, growth factors, vasoactive agents or extracellular matrix-forming proteins in ascites of cirrhotic patients [3][4][5][6]. In addition, several studies have demonstrated that the cellular component of ascites might influence the concentration of these substances [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its relatively simple composition [2], ascites has generally been considered to have little influence on the hemodynamic, and host defense abnormalities occurring in cirrhotic patients. This concept, however, has recently been challenged by several investigations describing significant amounts of proinflammatory cytokines, growth factors, vasoactive agents or extracellular matrix-forming proteins in ascites of cirrhotic patients [3][4][5][6]. In addition, several studies have demonstrated that the cellular component of ascites might influence the concentration of these substances [7][8][9].…”
Section: Introductionmentioning
confidence: 99%